Sensitivity and specificity of ANA and anti-dsDNA in the diagnosis of systemic lupus erythematosus: A comparison using control sera obtained from healthy individuals and patients with multiple medical problems - Wichainun,R. (The Allergy and Immunology Society of Thailand, 2015)
Background: Antinuclear antibodies (ANA) and anti-double stranded DNA (anti-dsDNA) are often tested as a screening tool in patients with suspected systemic lupus erythematosus or connective tissue diseases. ANA can be seen in healthy controls (HC) and patients with multiple medical problems (MMP). Objective: To determine the sensitivity and specificity of ANA and anti-dsDNA in SLE patients, using sera from HC and MMP patients. Methods: Serum samples from HC, MMP and SLE patients, 100 in each group, were analyzed for the presence of ANA and anti-dsDNA, by indirect immunofluorescent assay, using a HEp-2 cell and Crithidia luciliae as substrates, respectively. Results: The prevalence of ANA at a titer of ≥1:80 and ≥ 1:160 was 8% and 4%, respectively, in HC; and it was 12% and 6% respectively, in MMP patients. The prevalence of anti-dsDNA was 0% in HC and 3% in MMP patients. When using HC sera for the diagnosis of SLE, the sensitivity of ANA at a titer of ≥ 1:80 and ≥ 1:160 was 98% and 90%, respectively, with specificity of 92% and 96%, respectively. The specificity decreased to 88% and 94%, respectively, when using sera from MMP patients. The specificity of antidsDNA was 100% and 97%, when using sera from HC and MMP patients, respectively. Conclusion: ANA and anti-dsDNA gave high sensitivity and high specificity in patients with SLE, even when using MMP patient's sera as controls. Physicians should take care in interpreting ANA and anti-dsDNA results in MMP patients who do not have signs or symptoms of SLE or connective tissue diseases.